The Association Between Cytomegalovirus and Disability by Race/Ethnicity and Sex: Results From the Health and Retirement Study. Issue 11 (21st May 2021) - Duchowny, Kate A; Noppert, Grace A
Abstract: Recent studies have documented a decline in the overall prevalence of disability in the United States; however, racial/ethnic and sex disparities continue to persist. Cytomegalovirus (CMV) infection, a socially patterned exposure, may be a key mechanism in understanding these previously documented disparities. Using data from a nationally representative study, the 2016 Health and Retirement Study, we employed Poisson log-binomial models to estimate the prevalence of disability in a comparison of CMV-seropositive and -seronegative adults and investigated effect modification by race/ethnicity and sex. Among the 9, 029 participants (55% women; mean age = 67.4 years), 63% were CMV-seropositive and 15% were disabled. CMV seropositivity was highest among non-Hispanic Black (88%) and Hispanic (92%) adults as compared with non-Hispanic White adults (57%). We found evidence for effect modification in the association between CMV and disability by sex but not race/ethnicity. While the 95% confidence intervals in the fully adjusted models included the null value, in comparison with seronegative women, our results suggest a greater prevalence of disability among CMV-seropositive women (prevalence ratio = 1.16, 95% confidence interval: 0.97, 1.38) but not among men (prevalence ratio = 0.85, 95% confidence interval: 0.69, 1.06). Results provide initial support for the hypothesis that CMV may be an important determinant of sex disparities in disability.